The Effect of Service Quality on Customer Satisfaction on PT. Telkom Indonesia Tbk. Padang - Meri Dwi Anggreini; Mutia Amanda Ahmad; Agussalim Agussalim (Universitas Negeri Padang, 2021)
This study aims to determine the effect of service quality on customer satisfaction at PT. Telekomunikasi Indonesia, Tbk Padang. The data collection methods used in this research are field research and library research. Methods of data analysis in this study using simple regression. The population in this study was 40,013 consumers with a sample of 100 consumers. Based on the results of the analysis and discussion, it was found that the Service Quality variable (X) has a significant positive effect on Customer Satisfaction (Y) PT. Telekomunikasi Indonesia, Tbk Padang, it can be concluded that the variable service quality has a significant effect on customer satisfaction because the t value of the service quality variable is 5.714, which is greater than the t table value of 1.98447. So that t count> t table and the calculated sig value obtained is equal to 0.000 <0.05 so Ho is rejected Ha accepted.